Collaboration, problem solving and other 21st century skills for teaching of mathematics at secondary level - Portaankorva-Koivisto, Päivi; Viholainen, Antti (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
According to several views, collaboration and communication skills will be emphasized in the future. LUMATIKKA-project courses, directed for in-service mathematics teachers at grades 7–9 and high school, focus on future skills, so-called 21st century skills, like collaborative learning, mathematical languaging, modelling and problem solving. If these issues are emphasized in teaching of mathematics, learning may become more interactive, and it will activate students' own thinking more. Students will need these abilities to reason, justify, and illustrate their thinking in different ways. As well, formative assessment and especially feedback as part of teaching are very important issues. The LUMATIKKA-course directed for teaching of grades 7–9 is based on the idea of student-centered and active learning, and on the high school course, student-centeredness, as well, and meaningfulness are important themes. In this article, we will explain in more detail the importance of the content selected for these courses.